Ldh barrier
Patent Information
- Application Number
- CN202180045724.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-11
- Filing Date
- 2021-07-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-07-29
AI Technical Summary
像这样的由锌枝晶所引起的短路导致反复充放电寿命缩短
Smart Images

Figure GDA0004019533480000141 
Figure GDA0004019533480000151 
Figure GDA0004019533480000171
Abstract
Description
Technical Field
[0001] This invention relates to LDH partitions. Background Technology
[0002] It is known that in zinc secondary batteries such as nickel-zinc batteries and zinc-air batteries, during charging, metallic zinc precipitates in a dendritic form from the negative electrode, penetrating the gaps in the non-woven fabric or other separators to reach the positive electrode, resulting in a short circuit. Such short circuits caused by zinc dendrites shorten the battery life under repeated charge-discharge cycles.
[0003] To address the aforementioned problems, a battery has been proposed that includes a layered double hydroxide (LDH) separator, which allows hydroxide ions to selectively permeate while preventing zinc dendrites from penetrating. For example, Patent Document 1 (International Publication No. 2013 / 118561) discloses an LDH separator disposed between the positive and negative electrodes in a nickel-zinc secondary battery. Patent Document 2 (International Publication No. 2016 / 076047) discloses a separator structure comprising an LDH separator fitted or bonded to a resin frame, and further discloses that the LDH separator possesses high density, exhibiting a degree of air and / or water impermeability. This document also discloses that the LDH separator can be composited with a porous substrate. Patent Document 3 (International Publication No. 2016 / 067884) discloses various methods for forming a dense LDH film on the surface of a porous substrate to obtain a composite material (LDH separator). The method includes the following steps: uniformly attaching a starting material that can provide the crystal growth starting point for LDH to a porous substrate; and performing hydrothermal treatment on the porous substrate in a raw material aqueous solution to form a dense LDH film on the surface of the porous substrate.
[0004] Furthermore, LDH separators have been proposed in which further densification is achieved by rolling a composite material of LDH / porous substrate prepared by hydrothermal treatment. For example, Patent Document 4 (International Publication No. 2019 / 124270) discloses an LDH separator comprising a polymer porous substrate and LDH filled in the porous substrate, with a linear transmittance of 1% or more at a wavelength of 1000 nm. In this LDH separator, the pores of the porous substrate are fully blocked by LDH, thereby achieving a degree of densification that results in light transmittance, and thus more effectively suppressing short circuits caused by zinc dendrites. In addition, Patent Document 5 (International Publication No. 2019 / 124212) discloses an LDH separator comprising a polymer porous substrate and LDH filled in the porous substrate, having an average porosity of 0.03% or more and less than 1.0%.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: International Publication No. 2013 / 118561
[0008] Patent Document 2: International Publication No. 2016 / 076047
[0009] Patent Document 3: International Publication No. 2016 / 067884
[0010] Patent Document 4: International Publication No. 2019 / 124270
[0011] Patent Document 5: International Publication No. 2019 / 124212 Summary of the Invention
[0012] When using the highly densified LDH separator as described above to construct zinc secondary batteries such as nickel-zinc batteries, short circuits caused by zinc dendrites can be prevented to some extent. However, since LDH separators specifically utilize the hydroxide ion conductivity of hydroxide ion-conducting layered compounds such as LDH to selectively allow hydroxide ions to pass through, it is desirable not only to improve the density but also to further improve the ion conductivity.
[0013] Recently, the inventors of this invention have come to the insight that, in an LDH separator containing LDH and / or LDH-like compounds, namely hydroxide ion-conducting layered compounds, by making the proportion of hydroxide ion-conducting layered compounds in the LDH separator range from 25% to 85% by weight, it is possible to achieve both density and ion conductivity.
[0014] Therefore, the object of the present invention is to provide an LDH separator that has both good density and ionic conductivity.
[0015] According to one aspect of the present invention, an LDH separator is provided, comprising: a porous substrate and a hydroxide ion-conducting layered compound filling the pores of the porous substrate, wherein the hydroxide ion-conducting layered compound is a layered double hydroxide (LDH) and / or a layered double hydroxide (LDH)-like compound.
[0016] The LDH partition is characterized in that...
[0017] The hydroxide ion-conducting layered compound occupies 25-85% by weight in the LDH separator.
[0018] According to another aspect of the present invention, a zinc secondary battery is provided, characterized in that it comprises the above-mentioned LDH separator.
[0019] According to another aspect of the present invention, a solid alkaline fuel cell is provided, characterized in that it comprises the above-mentioned LDH separator. Attached Figure Description
[0020] Figure 1A This is a schematic diagram of an example of the He transmittance measurement system used in Examples A1 to E5.
[0021] Figure 1B yes Figure 1A The diagram shows a simplified cross-sectional view of the sample holder and its surrounding area used in the measurement system.
[0022] Figure 2 This is a simplified cross-sectional view of the electrochemical measurement system used in Examples A2 to E5. Detailed Implementation
[0023] LDH partition
[0024] The LDH separator of the present invention comprises: a porous substrate and a hydroxide ion-conducting layered compound filling the pores of the porous substrate. The hydroxide ion-conducting layered compound is a layered double hydroxide (LDH) and / or a layered double hydroxide (LDH)-like compound. In this specification, "LDH separator" is defined as a separator containing LDH and / or an LDH-like compound, specifically utilizing the hydroxide ion conductivity of LDH and / or the LDH-like compound to selectively allow hydroxide ions to pass through. In this specification, "LDH-like compound" refers to hydroxides and / or oxides that may not be called LDH but have a layered crystalline structure similar to LDH, and can be called equivalents of LDH. However, as a broad definition, "LDH" can also be interpreted as a substance containing LDH and LDH-like compounds. In the LDH separator, the LDH and / or LDH-like compound seals the pores of the porous substrate, making it exhibit hydroxide ion conductivity and impermeability (thus enabling it to function as an LDH separator exhibiting hydroxide ion conductivity). For example, the known LDH separators disclosed in Patent Documents 1 to 5 can be used. In summary, in LDH separators containing LDH and / or LDH-like compounds, i.e., hydroxide ion-conducting layered compounds, by making the proportion of hydroxide ion-conducting layered compounds in the LDH separator range from 25% to 85% by weight, it is possible to achieve both compactness and ion conductivity.
[0025] The proportion of the hydroxide ion-conducting layered compound in the LDH separator is 25–85% by weight, preferably 30–85% by weight, more preferably 35–85% by weight, and even more preferably 40–85% by weight. Within this range, both the density and ion conductivity of the LDH separator can be achieved more effectively. In particular, if the proportion of the hydroxide ion-conducting layered compound exceeds 85% by weight, the ion conductivity decreases significantly; however, according to the present invention, high ion conductivity can be achieved. Here, the proportion of the hydroxide ion-conducting layered compound in the LDH separator is a value calculated using [Wh / (Wh+Wp)]×100, where the weight of the hydroxide ion-conducting layered compound is Wh and the weight of the porous substrate is Wp.
[0026] For example, the ionic conductivity of the LDH separator is preferably 1.0 mS / cm or higher, more preferably 1.5 mS / cm or higher, even more preferably 2.0 mS / cm or higher, and particularly preferably 2.5 mS / cm or higher. Higher ionic conductivity is better; therefore, there is no upper limit, for example, 10 mS / cm.
[0027] On the other hand, the density of the LDH separator can be evaluated using He permeability. Specifically, the He permeability per unit area of the LDH separator is preferably 10 cm / min·atm or less, more preferably 5.0 cm / min·atm or less, and even more preferably 1.0 cm / min·atm or less. It can be said that an LDH separator with He permeability within such a range has very high density. Therefore, a separator with He permeability of 10 cm / min·atm or less can effectively prevent the passage of substances other than hydroxide ions. For example, in the case of a zinc secondary battery, it can very effectively suppress Zn permeation (typically the permeation of zinc ions or zincate ions) in the electrolyte. The He permeability is determined by the following steps: supplying He gas to one side of the separator to allow the He gas to pass through the separator, and calculating the He permeability to evaluate the density of the hydroxide ion-conducting separator. The He permeability is calculated using the formula F / (P×S) based on the permeation rate of He gas per unit time, the differential pressure P applied to the separator during He gas permeation, and the membrane area S through which He gas permeates. By evaluating gas permeability using He gas in this way, it is possible to assess whether extremely high levels of tightness exist. This effectively evaluates high tightness that minimizes the permeability of substances other than hydroxide ions (especially Zn, which causes zinc dendrite growth) (allowing only trace amounts to pass through). This is because He gas has the smallest constituent unit among the diverse atoms or molecules that can constitute a gas, and its reactivity is very low. That is, He does not form molecules but rather constitutes He gas as He atom monomers. In this respect, since hydrogen gas is composed of H2 molecules, He atom monomers are relatively small as gaseous constituent units. Since H2 gas is flammable, it is dangerous. Furthermore, by using an index such as the He gas permeability defined by the above formula, an objective evaluation of tightness can be easily performed regardless of various sample sizes and measurement conditions. This allows for a simple, safe, and effective evaluation of whether the separator has sufficiently high density suitable for zinc secondary batteries. The determination of He transmittance can preferably be performed according to the steps shown in Evaluation 5 of the following embodiment.
[0028] As described above, the LDH separator comprises: a porous substrate, and LDH and / or LDH-like compounds (hereinafter collectively referred to as hydroxide ion-conducting layered compounds). The hydroxide ion-conducting layered compounds are connected between the upper and lower surfaces of the LDH separator, thereby ensuring the hydroxide ion conductivity of the LDH separator. In the LDH separator, the hydroxide ion-conducting layered compounds seal the pores of the porous substrate; however, the pores of the porous substrate do not need to be completely sealed, and slight residual pores may remain.
[0029] LDH consists of multiple hydroxide base layers and intermediate layers between these base layers. The hydroxide base layers are primarily composed of metal elements (typically metal ions) and OH groups. The intermediate layers of LDH consist of anions and H₂O. The anions are valent to monovalent or higher, preferably monovalent or divalent ions. Preferably, the anions in LDH include OH groups. - and / or CO3 2- Furthermore, LDH possesses excellent ionic conductivity due to its inherent properties. Typically, LDH is known to be based on the fundamental formula M... 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (where M) 2+ M is a divalent cation. 3+ A is a trivalent cation. n- The substance represented by an n-valent anion (where n is an integer greater than or equal to 1, x is between 0.1 and 0.4, and m is greater than or equal to 0). In the above basic formula, M... 2+ It can be any divalent cation; as a preferred example, Mg can be cited. 2+ Ca 2+ and Zn 2+ More preferably Mg 2+ M 3+ It can be any trivalent cation; as a preferred example, Al can be cited. 3+ or Cr 3+ Al is preferred. 3+ A n- It can be any anion; as a preferred example, OH- - and CO3 2- Therefore, in the above basic formula, M is preferably... 2+ Contains Mg 2+ M 3+ Includes Al 3+ A n- Contains OH - and / or CO3 2- n is an integer greater than or equal to 1, preferably 1 or 2. x is 0.1 to 0.4, preferably 0.2 to 0.35. m is any number representing the number of moles of water, greater than or equal to 0, typically a real number greater than 0 or 1. However, the above basic composition is merely a formula representing the "basic composition" of LDH in a typical way, and the constituent ions can be appropriately substituted. For example, in the above basic composition, cations with a valence of 4 or higher (e.g., Ti) can be used. 4+ M 3+Partial or complete substitution can be performed, in which case the anion A in the above general formula can also be appropriately changed. n- The coefficient x / n.
[0030] For example, LDH exhibits excellent alkali resistance when its hydroxide base layer contains Mg, Al, Ti, and OH groups, which is particularly preferred. In this case, the hydroxide base layer can contain Mg, Al, Ti, and OH groups, or it can contain other elements or ions. For example, Y and / or Zn can be included in the LDH or hydroxide base layer. Furthermore, if the LDH or hydroxide base layer contains Y and / or Zn, Al or Ti may not be present in the LDH or hydroxide base layer. However, the hydroxide base layer preferably contains Mg, Al, Ti, and OH groups as its main constituent elements. That is, it is preferable that the hydroxide base layer mainly contains Mg, Al, Ti, and OH groups. Therefore, a typical design for the hydroxide base layer is composed of Mg, Al, Ti, OH groups, and impurities that are unavoidable depending on the circumstances. The atomic ratio of Ti / Al in the LDH, determined by energy dispersive X-ray analysis (EDS), is preferably 0.5 to 12, more preferably 1.0 to 12. If within the above range, ionic conductivity is not compromised, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite tolerance) can be achieved more effectively. For the same reason, the atomic ratio of Ti / (Mg+Ti+Al) in LDH, as determined by energy dispersive X-ray analysis (EDS), is preferably 0.1 to 0.7, more preferably 0.2 to 0.7. Furthermore, the atomic ratio of Al / (Mg+Ti+Al) in LDH is preferably 0.05 to 0.4, more preferably 0.05 to 0.25. Additionally, the atomic ratio of Mg / (Mg+Ti+Al) in LDH is preferably 0.2 to 0.7, more preferably 0.2 to 0.6. It should be noted that the EDS analysis is preferably performed as follows: using an EDS analysis device (e.g., X-act, Oxford Instruments), 1) acquire images at an accelerating voltage of 20kV and a magnification of 5,000x; 2) perform 3-point analysis in point analysis mode with an interval of about 5μm; 3) repeat steps 1) and 2) once more; 4) calculate the average value of a total of 6 points.
[0031] Alternatively, the hydroxide base layer of LDH can contain Ni, Al, Ti, and OH groups. In this case, the hydroxide base layer only needs to contain Ni, Al, Ti, and OH groups, but it can also contain other elements or ions. However, the hydroxide base layer preferably contains Ni, Al, Ti, and OH groups as the main constituent elements. That is, it is preferred that the hydroxide base layer mainly contains Ni, Al, Ti, and OH groups. Therefore, a typical scheme for the hydroxide base layer is: composed of Ni, Al, Ti, OH groups and impurities that are unavoidable depending on the situation. The atomic ratio of Ti / (Ni+Ti+Al) in LDH, determined by energy dispersive X-ray analysis (EDS), is preferably 0.10 to 0.90, more preferably 0.20 to 0.80, further preferably 0.25 to 0.70, and particularly preferably 0.30 to 0.61. If it is within the above range, both alkali resistance and ionic conductivity can be improved. Therefore, the hydroxide ion-conducting layered compound not only contains LDH, but also contains Ti to the extent that titanium dioxide is generated as a byproduct. That is, the hydroxide ion-conducting layered compound can further contain titanium dioxide. By containing titanium dioxide, hydrophilicity is improved, and improved wettability with the electrolyte (i.e., increased conductivity) can be expected.
[0032] The LDH-like compound is a hydroxide and / or oxide with a layered crystalline structure that, while perhaps not strictly LDH, resembles LDH. Preferably, it contains Mg and at least one element selected from the group consisting of Ti, Y, and Al, including Ti. By using a hydroxide and / or oxide with a layered crystalline structure containing at least Mg and Ti—that is, an LDH-like compound—instead of conventional LDH as the hydroxide ion-conducting material, a hydroxide ion-conducting barrier with excellent alkali resistance and the ability to more effectively suppress short circuits caused by zinc dendrites can be provided. Therefore, the preferred LDH-like compound is a hydroxide and / or oxide with a layered crystalline structure containing Mg and at least one element selected from the group consisting of Ti, Y, and Al, including Ti and / or Al. Thus, typical LDH-like compounds are complex hydroxides and / or complex oxides of Mg, Ti, Y (if desired), and Al (if desired), and particularly preferred are complex hydroxides and / or complex oxides of Mg, Ti, Y, and Al. The aforementioned elements can be replaced by other elements or ions to the extent that the basic properties of the LDH-like compound are not damaged; however, the LDH-like compound preferably does not contain Ni.
[0033] LDH-like compounds can be identified using X-ray diffraction. Specifically, when X-ray diffraction is performed on the surface of an LDH separator, peaks originating from LDH-like compounds are typically detected in the range of 5° ≤ 2θ ≤ 10°, and more typically in the range of 7° ≤ 2θ ≤ 10°. As mentioned above, LDH is a substance having an alternating layered structure with exchangeable anions and H2O as intermediate layers between stacked hydroxide base layers. In this regard, when LDH is determined by X-ray diffraction, peaks originating from the crystalline structure of LDH (i.e., the (003) peak of LDH) are typically detected at a position of 2θ = 11 to 12°. In contrast, when LDH-like compounds are determined by X-ray diffraction, peaks are typically detected in the range of the aforementioned range, which is shifted to a lower angle than the aforementioned peak position of LDH. Furthermore, using 2θ corresponding to the peaks originating from LDH-like compounds in X-ray diffraction, the interlayer distance of the layered crystalline structure can be determined according to the Bragg formula. The interlayer distances of the layered crystal structures that constitute LDH-like compounds are typically 0.883–1.8 nm, and more typically 0.883–1.3 nm.
[0034] The atomic ratio of Mg / (Mg+Ti+Y+Al) in the LDH-like compound, as determined by energy dispersive X-ray diffraction (EDS), is preferably 0.03 to 0.25, more preferably 0.05 to 0.2. Furthermore, the atomic ratio of Ti / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0.40 to 0.97, more preferably 0.47 to 0.94. Additionally, the atomic ratio of Y / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.45, more preferably 0 to 0.37. Moreover, the atomic ratio of Al / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.03. Within these ranges, the alkali resistance is superior, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite tolerance) can be achieved more effectively. However, regarding LDH separators, the basic composition of LDH, as previously known, can be expressed by the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (where M) 2+ M is a divalent cation. 3+ A is a trivalent cation. n-The term "anion with an n-valence, where n is an integer greater than or equal to 1, x is 0.1 to 0.4, and m is 0 or greater" is used. In contrast, the atomic ratios in LDH-like compounds generally deviate from the general formula for LDH. Therefore, it can be said that LDH-like compounds generally have different compositional ratios (atomic ratios) than conventional LDH. It should be noted that EDS analysis is preferably performed as follows: using an EDS analysis apparatus (e.g., X-act, Oxford Instruments), 1) acquire images at an accelerating voltage of 20 kV and a magnification of 5,000x; 2) perform 3-point analysis in point analysis mode with an interval of approximately 5 μm; 3) repeat steps 1) and 2) once more; 4) calculate the average value of the 6 points.
[0035] When an LDH separator is embedded in a zinc secondary battery, it separates the positive and negative plates in a manner that enables hydroxide ion conduction. Preferably, the LDH separator is impermeable to air and / or water. In other words, the LDH separator is preferably densified to a degree that makes it impermeable to air and / or water. It should be noted that "impermeable to air" in this specification means, as described in Patent Documents 2 and 3, that even when helium gas is brought into contact with one side of the test object in water at a differential pressure of 0.5 atm, no bubbles generated by the helium gas are observed on the other side. Furthermore, "impermeable to water" in this specification means, as described in Patent Documents 2 and 3, that water in contact with one side of the test object does not permeate to the other side. That is, the impermeability to air and / or water of the LDH separator means that the LDH separator has a high degree of densification to the point that no gas or water can pass through, and that it is not a porous membrane or other porous material that is permeable to water or air. Therefore, the LDH separator, due to its hydroxide ion conductivity, allows only selective passage of hydroxide ions, thus enabling it to function as a battery separator. This makes it an extremely effective configuration for preventing short circuits between the positive and negative electrodes by physically preventing separator penetration caused by zinc dendrites generated during charging. Because the LDH separator has hydroxide ion conductivity, it enables efficient movement of the required hydroxide ions between the positive and negative electrodes, thereby facilitating the charge-discharge reactions of both electrodes.
[0036] As described above, the LDH separator comprises a hydroxide ion-conducting layered compound and a porous substrate (typically composed of a porous substrate and the hydroxide ion-conducting layered compound). The hydroxide ion-conducting layered compound seals the pores of the porous substrate, thereby enabling the LDH separator to exhibit hydroxide ion conductivity and air tightness (thus functioning as a separator exhibiting hydroxide ion conductivity). The hydroxide ion-conducting layered compound is particularly preferably embedded throughout the entire thickness direction of the porous substrate. The thickness of the LDH separator is preferably 3–80 μm, more preferably 3–60 μm, and even more preferably 3–40 μm.
[0037] The porous substrate is preferably made of a polymer material. Polymer porous substrates have the following advantages: 1) flexibility (therefore, they are not prone to cracking even when thinned); 2) easy improvement of porosity; 3) easy improvement of conductivity (because it is possible to improve porosity and reduce thickness); 4) ease of manufacture and handling. Furthermore, by flexibly utilizing the advantage of flexibility mentioned above (1), it also has the following advantage: 5) the hydroxide ion-conducting separator comprising a porous substrate made of a polymer material can be easily bent or sealed. Preferred examples of polymer materials include: polystyrene, polyethersulfone, polypropylene, epoxy resin, polyphenylene sulfide, fluoropolymers (tetrafluoroethylene resins: PTFE, etc.), cellulose, nylon, polyethylene, and any combination thereof. From the viewpoint of thermoplastic resins suitable for heat pressing, more preferred examples include: polystyrene, polyethersulfone, polypropylene, epoxy resin, polyphenylene sulfide, fluoropolymers (tetrafluoroethylene resins: PTFE, etc.), nylon, polyethylene, and any combination thereof. All of the aforementioned preferred materials exhibit resistance to battery electrolytes, i.e., alkali resistance. Considering excellent resistance to hot water, acids, and alkalis, and low cost, polyolefins such as polypropylene and polyethylene are particularly preferred polymeric materials, with polypropylene or polyethylene being the most preferred. It is particularly preferred that the hydroxide ion-conducting layered compound is embedded throughout the entire thickness direction of the porous polymer substrate (e.g., most or almost all of the pores inside the porous polymer substrate are filled with the hydroxide ion-conducting layered compound). As such a porous polymer substrate, a commercially available polymeric microporous membrane is preferably used.
[0038] There is no particular limitation on the manufacturing method of LDH separators. They can be manufactured by directly or appropriately modifying the conditions (especially the composition of LDH raw materials) of known manufacturing methods of LDH separators (or functional layers containing LDH and composite materials) (see, for example, Patent Documents 1-5). For example, an LDH separator can be manufactured as follows: (1) a porous substrate is prepared; (2) a mixed sol of i) alumina and titanium dioxide (in the case of forming LDH) or ii) a solution containing titanium dioxide sol (or further containing yttrium sol and / or alumina sol) is applied to the porous substrate and dried to form a titanium dioxide layer; (3) the porous substrate is impregnated with a solution containing magnesium ions (Mg) 2+ ) and urea (or further containing yttrium ions (Y) 3+ (3) In the raw material aqueous solution; (4) The porous substrate is subjected to hydrothermal treatment in the raw material aqueous solution to form hydroxide ion-conducting layered compounds on and / or in the porous substrate. In addition, it is believed that: Urea is present in the above process (3), and ammonia is generated in the solution by the hydrolysis of urea, which increases the pH value. The coexisting metal ions form hydroxides and / or oxides, thereby obtaining hydroxide ion-conducting layered compounds (i.e., LDH and / or LDH-like compounds). In addition, the hydrolysis is accompanied by the generation of carbon dioxide. Therefore, in the case of LDH formation, LDH with carbonate ion type anions can be obtained.
[0039] In particular, when fabricating an LDH separator in which a hydroxide ion-conducting layered compound is embedded throughout the thickness of a porous polymer substrate, it is preferable to apply the mixed sol solution described in (2) to the substrate by a method that allows the mixed sol solution to penetrate the entire or most of the interior of the substrate. This allows most or almost all of the pores inside the porous substrate to be filled with the hydroxide ion-conducting layered compound. Examples of preferred coating methods include dip coating and filter coating, with dip coating being particularly preferred. The amount of mixed sol solution adhered can be adjusted by changing the number of coats applied in dip coating or similar methods. After drying the substrate coated with the mixed sol solution using dip coating or similar methods, the steps in (3) and (4) described above can be performed.
[0040] The LDH separators obtained by the above methods can be subjected to pressing treatment. This results in LDH separators with superior density. Pressing methods include, for example, roll pressing, uniaxial pressing, and CIP (cold isostatic pressing), without particular limitation, but roll pressing is preferred. By softening the porous polymer substrate, the pores of the porous polymer substrate can be fully sealed using hydroxide ion-conducting layered compounds. In this regard, it is preferable to perform the pressing while heating. For example, in the case of polypropylene and polyethylene, a heating temperature of 60°C to 200°C is preferred for sufficient softening. By performing pressing such as roll pressing within this temperature range, the residual pores in the LDH separator can be significantly reduced. As a result, the LDH separator can be made extremely dense, thus further effectively suppressing short circuits caused by zinc dendrites. During roll pressing, by appropriately adjusting the roll gap and roll temperature, the morphology of residual pores can be controlled, thereby obtaining an LDH separator with the desired density.
[0041] Zinc secondary battery
[0042] The LDH separator of the present invention is preferably applied to zinc secondary batteries. Therefore, according to a preferred embodiment of the present invention, a zinc secondary battery equipped with an LDH separator is provided. A typical zinc secondary battery includes a positive electrode, a negative electrode, and an electrolyte, with the positive and negative electrodes separated from each other by the LDH separator. The zinc secondary battery of the present invention is any secondary battery that uses zinc as the negative electrode and employs an electrolyte (typically an aqueous solution of an alkali metal hydroxide), and is not particularly limited. Therefore, it can be a nickel-zinc secondary battery, a silver-zinc oxide secondary battery, a manganese-zinc oxide secondary battery, a zinc-air secondary battery, or various other alkaline zinc secondary batteries. For example, preferably, the positive electrode contains nickel hydroxide and / or nickel hydroxyl oxide, thereby forming a nickel-zinc secondary battery. Alternatively, the positive electrode can be an air electrode, thereby forming a zinc-air secondary battery.
[0043] Solid alkaline fuel cells
[0044] The LDH separator of the present invention can also be applied to solid alkaline fuel cells. That is, by employing an LDH separator that highly densifies the pores of a porous substrate by sealing the pores with LDH, a solid alkaline fuel cell can be provided that effectively suppresses the decrease in electromotive force caused by fuel permeation to the air electrode side (e.g., methanol permeation). This is because the hydroxide ion conductivity of the LDH separator can be utilized, and the permeation of fuels such as methanol through the LDH separator is effectively suppressed. Therefore, according to another preferred embodiment of the present invention, a solid alkaline fuel cell equipped with an LDH separator is provided. A typical solid alkaline fuel cell according to this embodiment includes: an air electrode supplied with oxygen; a fuel electrode supplied with liquid fuel and / or gaseous fuel; and an LDH separator disposed between the fuel electrode and the air electrode.
[0045] Other batteries
[0046] Besides nickel-zinc batteries and solid alkaline fuel cells, the LDH separator of the present invention can also be used in, for example, nickel-metal hydride batteries. In this case, the LDH separator functions to impede nitride shuttle (the movement of nitrate groups between electrodes), which is the main cause of self-discharge in the battery. Furthermore, the LDH separator of the present invention can also be used in lithium batteries (batteries with lithium metal as the negative electrode), lithium-ion batteries (batteries with carbon or similar materials as the negative electrode), or lithium-air batteries, etc.
[0047] Example
[0048] The following illustrates an example of fabricating an LDH separator containing a layered compound that conducts hydroxide ions (LDH or LDH-like compounds). It should be noted that the evaluation method for the LDH separator is as follows.
[0049] Rating 1 Observation of microstructure
[0050] The surface microstructure of the LDH separator was observed using a scanning electron microscope (SEM, JSM-6610LV, manufactured by JEOL) at an accelerating voltage of 10–20 kV.
[0051] Rating 2 Elemental Analysis and Evaluation (EDS)
[0052] The surface composition of the LDH separator was analyzed using an EDS analyzer (X-act, Oxford Instruments). This confirmed the presence of specific elements in the crystal structure and calculated their atomic ratios. The analysis was performed as follows: 1) Images were acquired at an accelerating voltage of 20 kV and a magnification of 5,000x; 2) Three-point analysis was performed in point analysis mode with approximately 5 μm intervals; 3) Steps 1) and 2) were repeated once more.
[0053] Rating 3: Identification of hydroxide ion-conducting layered compounds
[0054] The crystalline phase of the hydroxide ion-conducting layered compound was determined using an X-ray diffraction apparatus (RINT TTR III, manufactured by Rigaku Corporation) under the following conditions: voltage: 50 kV, current: 300 mA, and measurement range: 10–70°. The XRD pattern was obtained.
[0055] Rating 4 The proportion of hydroxide ion-conducting layered compounds in the LDH separator
[0056] The weight of the LDH separator was measured, and the weight of the porous substrate alone was subtracted from the measured weight to calculate the weight of the hydroxide ion-conducting layered compound. The weight of the obtained hydroxide ion-conducting layered compound was divided by the weight of the LDH separator and multiplied by 100 to calculate the proportion of the hydroxide ion-conducting layered compound in the LDH separator.
[0057] Rating 5 He measured
[0058] To evaluate the compactness of the LDH separator from the perspective of He permeability, a He permeability test was conducted as follows. First, the structure was constructed... Figure 1A and Figure 1B The He transmittance measurement system 310 is shown. The He transmittance measurement system 310 is configured such that He gas from a gas cylinder filled with He gas is supplied to the sample holder 316 via a pressure gauge 312 and a flow meter 314 (digital flow meter), and is discharged from one side of the LDH partition 318 held on the sample holder 316 to the other side.
[0059] The sample holder 316 has a structure including a gas supply port 316a, a sealed space 316b, and a gas outlet 316c, and is assembled as follows. First, an adhesive 322 is applied along the outer periphery of the LDH partition 318, and it is mounted on a clamp 324 (made of ABS resin) with a central opening. Butyl rubber seals are provided at the upper and lower ends of the clamp 324 as sealing members 326a and 326b. Then, support members 328a and 328b (made of PTFE) with openings formed by flanges are used to clamp the sample holder from the outside of the sealing members 326a and 326b. In this way, the sealed space 316b is divided by the LDH partition 318, the clamp 324, the sealing member 326a, and the support member 328a. The support members 328a and 328b are fastened to each other by using a screw fastening mechanism 330, so that He gas will not leak from any part other than the gas outlet 316c. The gas supply port 316a of the sample holder 316 assembled in this way is connected to a gas supply pipe 334 by means of a connector 332.
[0060] Next, He gas is supplied to the He permeability measurement system 310 via gas supply pipe 334, allowing it to pass through the LDH partition 318 held within the sample holder 316. During this time, the gas supply pressure and flow rate are monitored using pressure gauge 312 and flow meter 314. After He gas permeation for 1–30 minutes, the He permeability is calculated. The calculation of the He permeability uses the He gas permeation rate F (cm³) per unit time. 3The differential pressure P (atm) applied to the LDH separator during He gas permeation, and the membrane area S (cm²) during He gas permeation. 2 The permeation rate of He gas, F (cm³), is calculated using the formula F / (P×S). 3 The flow rate ( / min) is read directly from flow meter 314. Additionally, the differential pressure P is measured using gauge pressure from pressure gauge 312. It should be noted that He gas is supplied with a differential pressure P ranging from 0.05 to 0.90 atm.
[0061] Rating 6 Determination of ionic conductivity
[0062] use Figure 2 The electrochemical measurement system shown was used to determine the conductivity of the LDH separator in the electrolyte as follows. The LDH separator sample S was clamped from both sides by silicone sealants 440 with a thickness of 1 mm and installed in a PTFE flanged electrolytic cell 442 with an inner diameter of 6 mm. As electrodes 446, a #100 mesh nickel mesh was installed in the electrolytic cell 442 in a cylindrical shape with a diameter of 6 mm, with a distance of 2.2 mm between electrodes. As the electrolyte 444, a 6M KOH aqueous solution was filled into the electrolytic cell 442. The measurement was performed using an electrochemical measurement system (constant voltage / constant current-frequency response analyzer, Solartron 1287A and 1255B models) under conditions of a frequency range of 1 MHz to 0.1 Hz and an applied voltage of 10 mV. The intercept of the real number axis was used as the resistance of the composite sample S. The same measurement was performed with a sample S without an LDH separator to determine the blank resistance. The difference between the resistance of the LDH separator sample S and the blank resistance is taken as the resistance of the LDH separator. Using the obtained resistance, thickness, and area of the LDH separator, the conductivity is calculated.
[0063] Example A1~A7
[0064] The following describes the fabrication and evaluation of LDH separators containing Mg-Ti-type LDH compounds.
[0065] (1) Preparation of porous polymer substrate
[0066] A commercially available polyethylene microporous membrane with a porosity of 50%, an average pore diameter of 0.1 μm, and a thickness of 10 μm was prepared as a polymer porous substrate and cut into 5.0 cm × 5.0 cm pieces.
[0067] (2) Coating titanium dioxide sol onto a porous polymer substrate
[0068] Titanium dioxide sol solution (AM-15, manufactured by Tagi Chemical Co., Ltd.) was applied to the substrate prepared in (1) above by dip coating. The dip solution was prepared by mixing titanium dioxide sol and deionized water at the weight ratios shown in Table 1. The dip coating was performed by immersing the substrate in 100 mL of the dip solution and then vertically lifting it as shown in Table 1. The dip-coated substrate was then dried at room temperature for 1 hour.
[0069] (3) Preparation of raw material aqueous solution
[0070] Magnesium nitrate hexahydrate (Mg(NO3)2·6H2O, manufactured by Kanto Chemical Co., Ltd.) and urea ((NH2)2CO, manufactured by Sigma Aldrich) were prepared as raw materials. The concentrations of magnesium nitrate hexahydrate (0.0075 mol / L) and urea / NO3 were... - Weigh the raw material using a (mol ratio) of 96 and place it in a beaker. Add ion-exchanged water to bring the total volume to 80 mL. Then, stir to obtain an aqueous solution of the raw material.
[0071] (4) Film formation by hydrothermal treatment
[0072] The raw material aqueous solution and the impregnated substrate are sealed together in a Teflon (registered trademark) sealed container (autoclave container, internal volume 100mL, outer sleeve of stainless steel). The substrate is then floated from the bottom of the Teflon (registered trademark) sealed container and fixed in place, vertically positioned so that the solution is in contact with both sides of the substrate. A hydrothermal treatment is then performed at 90°C for 10 hours, thereby forming an LDH-like compound on the surface and inside the substrate. After the specified time, the substrate is removed from the sealed container, washed with deionized water, and dried overnight at room temperature, thereby forming an LDH-like compound within the pores of the porous substrate. This yields the LDH separator.
[0073] (5) Densification is achieved by rolling.
[0074] The LDH separator was clamped between a pair of PET films (manufactured by Toray Industries, Inc., Lumirror (registered trademark), 40 μm thick) and rolled at a roller rotation speed of 3 mm / s, a roller heating temperature of 70 °C, and a roller gap of 70 μm to obtain a further densified LDH separator.
[0075] (6) Various evaluations
[0076] The obtained LDH separators were evaluated according to evaluations 1 through 6. It should be noted that, regarding Example A1, the expected compactness was not observed in evaluation 5; therefore, evaluation 6 was not performed. The results are as follows.
[0077] - Evaluation 1: A large number of LDH-specific plate-like crystals were confirmed.
[0078] - Evaluation 2: The results of EDS elemental analysis showed that Mg and Ti were detected as constituent elements of LDH-like compounds. That is, these elements were confirmed to have entered and crystallized in the form of hydroxide ion-conducting layered compounds.
[0079] - Evaluation 3: In the XRD pattern, peaks originating from LDH-like compounds were detected in the range of 5° ≤ 2θ ≤ 10°. Typically, the (003) peak of LDH is observed at 2θ = 11–12°. Therefore, it is believed that the above peaks are obtained by shifting the (003) peak of LDH to a lower angle. This suggests that the above peaks originate from compounds that, while not technically LDH, are similar to LDH (i.e., LDH-like compounds).
[0080] - Evaluation 4: The proportion of hydroxide ion-conducting layered compounds in the LDH separator is shown in Table 2.
[0081] - Evaluation 5: As shown in Table 2, except for Example A1 (Comparative Example), the extremely high density of He with a transmittance of 0.00 cm / min·atm was confirmed.
[0082] - Evaluation 6: As shown in Table 2, a higher ionic conductivity was confirmed in Examples A3 to A7 compared to Comparative Example A2. Table 2 shows a trend where increasing the weight of the hydroxide ion-conducting layered compound increases ionic conductivity (i.e., improves performance). However, near Example A5 (62% by weight of the hydroxide ion-conducting layered compound), the ionic conductivity reaches a peak, and thereafter, increasing the weight of the hydroxide ion-conducting layered compound decreases ionic conductivity.
[0083] Table 1
[0084] Table 1
[0085]
[0086] * indicates a comparison example.
[0087] Table 2
[0088] Table 2
[0089]
[0090] * indicates a comparison example.
[0091] Furthermore, as shown in Table 2, by making the proportion of the hydroxide ion-conducting layered compound in the LDH separator range from 25% to 85% by weight, it is possible to achieve both high density (e.g., He permeability below 10 cm / min·atm) and high ion conductivity (e.g., above 1 mS / cm).
[0092] Examples B1~B5
[0093] The following describes the fabrication and evaluation of LDH separators containing Mg-(Ti, Y)- type LDH compounds.
[0094] (1) Preparation of porous polymer substrate
[0095] A commercially available polyethylene microporous membrane with a porosity of 50%, an average pore diameter of 0.1 μm, and a thickness of 10 μm was prepared as a polymer porous substrate and cut into 5.0 cm × 5.0 cm pieces.
[0096] (2) Coating titanium dioxide-yttrium oxide sol onto a porous polymer substrate
[0097] Titanium dioxide sol solution (AM-15, manufactured by Tagi Chemical Co., Ltd.) and yttrium oxide sol were coated onto the substrate prepared in (1) above by dip coating. The dip solution was prepared by mixing the titanium dioxide sol solution and yttrium oxide sol at a Ti / Y (mol ratio) of 4 and mixing them with ion-exchanged water at the weight ratio shown in Table 3. The dip coating was performed by immersing the substrate in 100 mL of the dip solution and then vertically lifting it as shown in Table 3. The dip-coated substrate was then dried at room temperature for 1 hour.
[0098] (3) Preparation of raw material aqueous solution
[0099] Magnesium nitrate hexahydrate (Mg(NO3)2·6H2O, manufactured by Kanto Chemical Co., Ltd.) and urea ((NH2)2CO, manufactured by Sigma Aldrich) were prepared as raw materials. The concentrations of magnesium nitrate hexahydrate (0.0075 mol / L) and urea / NO3 were... - Weigh the raw material using a (mol ratio) of 96 and place it in a beaker. Add ion-exchanged water to bring the total volume to 80 mL. Then, stir to obtain an aqueous solution of the raw material.
[0100] (4) Film formation by hydrothermal treatment
[0101] The raw material aqueous solution and the impregnated substrate are sealed together in a Teflon (registered trademark) sealed container (autoclave container, internal volume 100mL, outer sleeve of stainless steel). The substrate is then floated from the bottom of the Teflon (registered trademark) sealed container and fixed in place, vertically positioned so that the solution is in contact with both sides of the substrate. A hydrothermal treatment is then performed at 120°C for 16 hours, thereby forming an LDH-like compound on the surface and inside the substrate. After the specified time, the substrate is removed from the sealed container, washed with deionized water, and dried overnight at room temperature, thereby forming an LDH-like compound within the pores of the porous substrate. This yields the LDH separator.
[0102] (5) Densification is achieved by rolling.
[0103] The LDH separator was clamped between a pair of PET films (manufactured by Toray Industries, Inc., Lumirror (registered trademark), 40 μm thick) and rolled at a roller rotation speed of 3 mm / s, a roller heating temperature of 70 °C, and a roller gap of 70 μm to obtain a further densified LDH separator.
[0104] (6) Various evaluations
[0105] The obtained LDH partitions were evaluated using criteria 1 to 6. The results are as follows.
[0106] - Evaluation 1: A large number of LDH-specific plate-like shapes were confirmed.
[0107] - Evaluation 2: The results of EDS elemental analysis showed that Mg, Ti, and Y were detected as constituent elements of LDH-like compounds. That is, these elements were confirmed to have entered and crystallized in the form of hydroxide ion-conducting layered compounds.
[0108] - Evaluation 3: In the XRD pattern, peaks originating from LDH-like compounds were detected in the range of 5° ≤ 2θ ≤ 10°. Typically, the (003) peak of LDH is observed at 2θ = 11–12°. Therefore, it is believed that the above peaks are obtained by shifting the (003) peak of LDH to a lower angle. This suggests that the above peaks originate from compounds that, while not technically LDH, are similar to LDH (i.e., LDH-like compounds).
[0109] - Evaluation 4: The proportion of hydroxide ion-conducting layered compounds in the LDH separator is shown in Table 4.
[0110] - Evaluation 5: As shown in Table 4, the extremely high density of He with a transmittance of 0.00 cm / min·atm was confirmed.
[0111] - Evaluation 6: As shown in Table 4, the higher ionic conductivity of the proportion B1 (comparative example) was confirmed in Examples B2 to B5.
[0112] Table 3
[0113] Table 3
[0114]
[0115] * indicates a comparison example.
[0116] Table 4
[0117] Table 4
[0118]
[0119] * indicates a comparison example.
[0120] Examples C1 to C5
[0121] The following describes the fabrication and evaluation of an LDH separator containing Mg-(Al, Ti)-LDH.
[0122] (1) Preparation of porous polymer substrate
[0123] A commercially available polyethylene microporous membrane with a porosity of 50%, an average pore diameter of 0.1 μm, and a thickness of 10 μm was prepared as a polymer porous substrate and cut into 5.0 cm × 5.0 cm pieces.
[0124] (2) Coating alumina-titanium dioxide sol onto a polymer porous substrate
[0125] Amorphous alumina solution (Al-L7, manufactured by Tagi Chemical Co., Ltd.) and titanium dioxide sol solution (AM-15, manufactured by Tagi Chemical Co., Ltd.) were applied to the substrate prepared in (1) above by dip coating. The dip solution was prepared by mixing the amorphous alumina solution and the titanium dioxide sol solution at a Ti / Al (mol ratio) of 2 and mixing them with ion-exchanged water at the weight ratio shown in Table 5. The dip coating was performed by immersing the substrate in 100 mL of the dip solution and then vertically lifting it as shown in Table 5. The dip-coated substrate was then dried at room temperature for 1 hour.
[0126] (3) Preparation of raw material aqueous solution
[0127] Magnesium nitrate hexahydrate (Mg(NO3)2·6H2O, manufactured by Kanto Chemical Co., Ltd.) and urea ((NH2)2CO, manufactured by Sigma Aldrich) were prepared as raw materials. The concentrations of magnesium nitrate hexahydrate (0.015 mol / L) and urea / NO3 were... -Weigh the raw materials using a (mol ratio) of 32 and place them in a beaker. Add ion-exchanged water to bring the total volume to 80 mL. Then, stir to obtain an aqueous solution of the raw materials.
[0128] (4) Film formation by hydrothermal treatment
[0129] The raw material aqueous solution and the impregnated substrate are sealed together in a Teflon (registered trademark) sealed container (autoclave container, internal volume 100mL, outer stainless steel sleeve). The substrate is then floated from the bottom of the Teflon (registered trademark) sealed container and fixed in place, vertically positioned so that the solution is in contact with both sides of the substrate. A hydrothermal treatment is then performed at 120°C for 16 hours, thereby forming LDH on the surface and inside the substrate. After the specified time, the substrate is removed from the sealed container, washed with deionized water, and dried overnight at room temperature, thereby forming LDH within the pores of the porous substrate. This yields the LDH separator.
[0130] (5) Densification is achieved by rolling.
[0131] The LDH separator was clamped between a pair of PET films (manufactured by Toray Industries, Inc., Lumirror (registered trademark), 40 μm thick) and rolled at a roller rotation speed of 3 mm / s, a roller heating temperature of 70 °C, and a roller gap of 70 μm to obtain a further densified LDH separator.
[0132] (6) Various evaluations
[0133] The obtained LDH partitions were evaluated using criteria 1 to 6. The results are as follows.
[0134] - Evaluation 1: A large number of LDH-specific plate-like crystals were confirmed.
[0135] - Evaluation 2: The results of EDS elemental analysis showed that Mg, Al, and Ti, which are constituent elements of LDH, were detected. That is, these elements were confirmed to have entered and crystallized in the form of hydroxide ion-conducting layered compounds.
[0136] - Evaluation 3: A peak was detected near 2θ = 11.5° in the XRD pattern, identified as LDH (hydrotalcite compound). This identification was performed using the diffraction peaks of LDH (hydrotalcite compound) described in JCPDS Card NO. 35-0964.
[0137] - Evaluation 4: The proportion of hydroxide ion-conducting layered compounds in the LDH separator is shown in Table 6.
[0138] - Evaluation 5: As shown in Table 6, the extremely high density of He with a transmittance of 0.0 cm / min·atm was confirmed.
[0139] - Evaluation 6: As shown in Table 6, the higher ionic conductivity of C1 was confirmed in Examples C2 to C5.
[0140] Table 5
[0141] Table 5
[0142]
[0143] * indicates a comparison example.
[0144] Table 6
[0145] Table 6
[0146]
[0147] * indicates a comparison example.
[0148] Examples D1~D5
[0149] The following describes the fabrication and evaluation of LDH separators containing Mg-(Al, Ti, Y)-type LDH compounds.
[0150] (1) Preparation of porous polymer substrate
[0151] A commercially available polyethylene microporous membrane with a porosity of 50%, an average pore diameter of 0.1 μm, and a thickness of 10 μm was prepared as a polymer porous substrate and cut into 5.0 cm × 5.0 cm pieces.
[0152] (2) Coating an alumina-titanium dioxide-yttrium oxide sol onto a porous polymer substrate.
[0153] Amorphous alumina solution (Al-L7, manufactured by Tagi Chemical Co., Ltd.), titanium dioxide solution (AM-15, manufactured by Tagi Chemical Co., Ltd.), and yttrium oxide sol were applied to the substrate prepared in (1) above by dip coating. The dip coating solution was prepared by mixing the amorphous alumina solution, titanium dioxide solution, and yttrium oxide sol at a ratio of Ti / (Y+Al) (mol ratio) = 2 and Y / Al (mol ratio) = 8, and mixing them with ion-exchanged water at the weight ratios shown in Table 7. The dip coating was performed by immersing the substrate in 100 ml of the dip coating solution and then vertically lifting it as shown in Table 7. The dip-coated substrate was then dried at room temperature for 1 hour.
[0154] (3) Preparation of raw material aqueous solution
[0155] Magnesium nitrate hexahydrate (Mg(NO3)2·6H2O, manufactured by Kanto Chemical Co., Ltd.) and urea ((NH2)2CO, manufactured by Sigma Aldrich) were prepared as raw materials. The concentrations of magnesium nitrate hexahydrate (0.0075 mol / L) and urea / NO3 were... - Weigh the raw material using a (mol ratio) of 96 and place it in a beaker. Add ion-exchanged water to bring the total volume to 80 mL. Then, stir to obtain an aqueous solution of the raw material.
[0156] (4) Film formation by hydrothermal treatment
[0157] The raw material aqueous solution and the impregnated substrate are sealed together in a Teflon (registered trademark) sealed container (autoclave container, internal volume 100mL, outer sleeve of stainless steel). The substrate is then floated from the bottom of the Teflon (registered trademark) sealed container and fixed in place, vertically positioned so that the solution is in contact with both sides of the substrate. A hydrothermal treatment is then performed at 120°C for 16 hours, thereby forming an LDH-like compound on the surface and inside the substrate. After the specified time, the substrate is removed from the sealed container, washed with deionized water, and dried overnight at room temperature, thereby forming an LDH-like compound within the pores of the porous substrate. This yields the LDH separator.
[0158] (5) Densification is achieved by rolling.
[0159] The LDH separator was clamped between a pair of PET films (manufactured by Toray Industries, Inc., Lumirror (registered trademark), 40 μm thick) and rolled at a roller rotation speed of 3 mm / s, a roller heating temperature of 70 °C, and a roller gap of 70 μm to obtain a further densified LDH separator.
[0160] (6) Various evaluations
[0161] The obtained LDH partitions were evaluated using criteria 1 to 6. The results are as follows.
[0162] - Evaluation 1: A large number of LDH-specific plate-like shapes were confirmed.
[0163] - Evaluation 2: The results of EDS elemental analysis showed that Mg, Al, Ti, and Y were detected as constituent elements of LDH-like compounds. That is, these elements were confirmed to have entered and crystallized in the form of hydroxide ion-conducting layered compounds.
[0164] - Evaluation 3: In the XRD pattern, peaks originating from LDH-like compounds were detected in the range of 5° ≤ 2θ ≤ 10°. Typically, the (003) peak of LDH is observed at 2θ = 11–12°. Therefore, it is believed that the above peaks are obtained by shifting the (003) peak of LDH to a lower angle. This suggests that the above peaks originate from compounds that, while not technically LDH, are similar to LDH (i.e., LDH-like compounds).
[0165] - Evaluation 4: The proportion of hydroxide ion-conducting layered compounds in the LDH separator is shown in Table 8.
[0166] - Evaluation 5: As shown in Table 8, the extremely high density of He with a transmittance of 0.0 cm / min·atm was confirmed.
[0167] - Evaluation 6: As shown in Table 8, the higher ionic conductivity of the proportion D1 (comparative example) was confirmed in examples D2 to D5.
[0168] Table 7
[0169] Table 7
[0170]
[0171] * indicates a comparison example.
[0172] Table 8
[0173] Table 8
[0174]
[0175] * indicates a comparison example.
[0176] Examples E1~E5
[0177] The following describes the fabrication and evaluation of an LDH separator containing Ni-(Al, Ti)-LDH.
[0178] (1) Preparation of porous polymer substrate
[0179] A commercially available polyethylene microporous membrane with a porosity of 50%, an average pore diameter of 0.1 μm, and a thickness of 10 μm was prepared as a polymer porous substrate and cut into 5.0 cm × 5.0 cm pieces.
[0180] (2) Coating alumina-titanium dioxide sol onto a polymer porous substrate
[0181] Amorphous alumina solution (Al-L7, manufactured by Tagi Chemical Co., Ltd.) and titanium dioxide sol solution (AM-15, manufactured by Tagi Chemical Co., Ltd.) were applied to the substrate prepared in (1) above by dip coating. The dip solution was prepared by mixing the amorphous alumina solution and the titanium dioxide sol solution at a Ti / Al (mol ratio) of 2 and mixing them with ion-exchanged water at the weight ratio shown in Table 9. The dip coating was performed by repeatedly immersing the substrate in 100 mL of the dip solution and then vertically lifting it as shown in Table 9. The dip-coated substrate was then dried at room temperature for 1 hour.
[0182] (3) Preparation of raw material aqueous solution
[0183] Nickel nitrate hexahydrate (Ni(NO3)2·6H2O, manufactured by Kanto Chemical Co., Ltd.) and urea ((NH2)2CO, manufactured by Sigma Aldrich) were prepared as raw materials. The concentrations of nickel nitrate hexahydrate (0.0075 mol / L) and urea / NO3 were... - Weigh the raw materials using a (mol ratio) of 16 and place them in a beaker. Add ion-exchanged water to bring the total volume to 80 mL. Then, stir to obtain an aqueous solution of the raw materials.
[0184] (4) Film formation by hydrothermal treatment
[0185] The raw material aqueous solution and the impregnated substrate are sealed together in a Teflon (registered trademark) sealed container (autoclave container, internal volume 100mL, outer stainless steel sleeve). The substrate is then floated from the bottom of the Teflon (registered trademark) sealed container and fixed in place, vertically positioned so that the solution is in contact with both sides of the substrate. A hydrothermal treatment is then performed at 120°C for 16 hours, thereby forming LDH on the surface and inside the substrate. After the specified time, the substrate is removed from the sealed container, washed with deionized water, and dried overnight at room temperature, thereby forming LDH within the pores of the porous substrate. This yields the LDH separator.
[0186] (5) Densification is achieved by rolling.
[0187] The LDH separator was clamped between a pair of PET films (manufactured by Toray Industries, Inc., Lumirror (registered trademark), 40 μm thick) and rolled at a roller rotation speed of 3 mm / s, a roller heating temperature of 70 °C, and a roller gap of 70 μm to obtain a further densified LDH separator.
[0188] (6) Various evaluations
[0189] The obtained LDH partitions were evaluated using criteria 1 to 6. The results are as follows.
[0190] - Evaluation 1: A large number of LDH-specific plate-like crystals were confirmed.
[0191] - Evaluation 2: The results of EDS elemental analysis showed that Ni, Al, and Ti, as constituent elements of LDH, were detected. That is, these elements were confirmed to have entered and crystallized in the form of hydroxide ion-conducting layered compounds.
[0192] - Evaluation 3: A peak was detected near 2θ = 11.5° in the XRD pattern, identified as LDH (hydrotalcite compound). This identification was performed using the diffraction peaks of LDH (hydrotalcite compound) described in JCPDS Card NO. 35-0964.
[0193] - Evaluation 4: The proportion of hydroxide ion-conducting layered compounds in the LDH separator is shown in Table 10.
[0194] - Evaluation 5: As shown in Table 10, the extremely high density of He with a transmittance of 0.0 cm / min·atm was confirmed.
[0195] - Evaluation 6: As shown in Table 10, the high ionic conductivity of E1 (comparative example) was confirmed in Examples E2 to E5.
[0196] Table 9
[0197] Table 9
[0198]
[0199] * indicates a comparison example.
[0200] Table 10
[0201]
[0202] * indicates a comparison example.
[0203] Summary of Results
[0204] The results shown in Tables 2, 4, 6, 8, and 10 indicate that, regardless of the constituent elements of the hydroxide ion-conducting layered compound, the same correlation is observed between the proportion of the hydroxide ion-conducting layered compound in the LDH separator and ionic conductivity. Specifically, the following trend is observed: increasing the proportion of the hydroxide ion-conducting layered compound in the LDH separator increases ionic conductivity (i.e., improves performance). However, the ionic conductivity peaks near a proportion of approximately 60% by weight, and thereafter, increasing the weight of the hydroxide ion-conducting layered compound leads to a steady decrease in ionic conductivity.
Claims
1. An LDH separator, comprising: A porous substrate and a hydroxide ion-conducting layered compound filling the pores of the porous substrate, wherein the hydroxide ion-conducting layered compound is a layered double hydroxide (LDH) compound. The LDH partition is characterized in that... The hydroxide ion-conducting layered compound occupies 25-85% by weight in the LDH separator. The LDH-like compound is a layered crystalline hydroxide and / or oxide containing Mg and the element selected from the group consisting of Ti, Y, and Al, which includes at least one element containing Ti. When the surface of the LDH separator is subjected to X-ray diffraction, peaks originating from the LDH-like compound are detected in the range of 5°≤2θ≤10°.
2. The LDH partition according to claim 1, characterized in that, The hydroxide ion-conducting layered compound occupies 30-85% by weight in the LDH separator.
3. The LDH partition according to claim 1 or 2, characterized in that, The porous substrate is composed of polymer materials.
4. The LDH partition according to claim 3, characterized in that, The polymer material is selected from the group consisting of polystyrene, polyethersulfone, polypropylene, epoxy resin, polyphenylene sulfide, fluoropolymer, cellulose, nylon, and polyethylene.
5. A zinc secondary battery, characterized in that, It has an LDH partition as described in any one of claims 1 to 4.
6. A solid alkaline fuel cell, characterized in that, It has an LDH partition as described in any one of claims 1 to 4.
Citation Information
Patent Citations
Zinc secondary cell
WO2013118561A1
Method for forming layered double hydroxide dense membrane
WO2016067884A1
Separator structure body for use in zinc secondary battery
WO2016076047A1
LDH separator and zinc secondary cell
WO2019124212A1
LDH separator and zinc secondary battery
WO2019124270A1